2014
DOI: 10.1021/ja502221r
|View full text |Cite
|
Sign up to set email alerts
|

Effective Ligand Passivation of Cu2O Nanoparticles through Solid-State Treatment with Mercaptopropionic Acid

Abstract: In colloidal nanoparticle (NPs) devices, trap state densities at their surface exert a profound impact on the rate of charge carrier recombination and, consequently, on the deterioration of the device performance. Here, we report on the successful application of a ligand exchange strategy to effectively passivate the surface of cuprite (Cu2O) NPs. Cu2O NPs were prepared by means of a novel synthetic route based on flame spray pyrolysis. FTIR, XRD, XPS, and HRTEM measurements corroborate the formation of cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…[8][9][10] For instance, it is shown that the direction of the vertical segregation in organic bulk-heterojunction (oBHJ) can be effectively controlled by modifying the surface energy. [8][9][10] For instance, it is shown that the direction of the vertical segregation in organic bulk-heterojunction (oBHJ) can be effectively controlled by modifying the surface energy.…”
Section: Doi: 101002/aenm201401692mentioning
confidence: 99%
“…[8][9][10] For instance, it is shown that the direction of the vertical segregation in organic bulk-heterojunction (oBHJ) can be effectively controlled by modifying the surface energy. [8][9][10] For instance, it is shown that the direction of the vertical segregation in organic bulk-heterojunction (oBHJ) can be effectively controlled by modifying the surface energy.…”
Section: Doi: 101002/aenm201401692mentioning
confidence: 99%
“…Here, contrary to the previous two semiconductors, novel optical properties and photocurrent generation are expected from the hybrid material studied in under band gap excitation conditions. Nevertheless, one has to also consider that nanoparticles in contact with the CNT may undergo surface passivation along with corresponding changes in the electron trap states within the band gap [ 35 ]. Furthermore, since the CNTs are not functionalized in the present study, a direct insight into the role of intrinsic defects in the as-grown CNTs can be attained in the process of attaching nanoparticles to their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the excitonic peak seen at 545 nm vanishes and the bandgap ( E g ) shifts towards the bulk value for CIS. [ 24,25 ] Second, EDX and Raman data infer that higher annealing temperatures lead to the conversion from copper-defi cient to copper-rich CIS NC fi lms. The broadness of the PL implies a rather large-size distribution, [ 21 ] which is consistent with the observation of two absorption peaks at 545 and 740 nm.…”
Section: Introductionmentioning
confidence: 99%